2013
DOI: 10.1007/s11626-013-9659-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide regulates biosynthesis of cystathionine γ-lyase and hydrogen sulfide through toll-like receptor-4/p38 and toll-like receptor-4/NF-κB pathways in macrophages

Abstract: Hydrogen sulfide (H2S), formed mainly by the enzyme cystathionine γ-lyase (CSE) in macrophages, is emerging as a novel regulator in inflammation. Although elevated production of H2S has been shown in inflammatory processes, the underlying molecular mechanism remains to be further elucidated. In this study, we compared parallel TLR4 knockout (TLR4(-/-)) mice with their wild-type counterparts following lipopolysaccharide (LPS) treatment. It showed that LPS increased the expressions of CSE and biosynthesis of H2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…Recently, NF- κ B has been shown to be involved in TLR4-mediated upregulation of CSE mRNA expression and generation of hydrogen sulfide in LPS-induced macrophages [36]. In accordance with this report, our findings also suggest that NF- κ B plays a key role in the inflammatory response of LPS-induced macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, NF- κ B has been shown to be involved in TLR4-mediated upregulation of CSE mRNA expression and generation of hydrogen sulfide in LPS-induced macrophages [36]. In accordance with this report, our findings also suggest that NF- κ B plays a key role in the inflammatory response of LPS-induced macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorylation of ERK increased as early as 15 min after LPS treatment and reached a peak at 30 min which was in accordance with previous reports [35, 36]. However, it is of interest to note that inhibition of hydrogen sulfide production by silencing the CSE gene using siRNA in cells treated with LPS for 30 min resulted in reduced phosphorylation of ERK.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, and in relation to previous studies showing a relationship between H 2 S and TLR4, activation with LPS induces an increase in CSE expression and the free sulfide levels in colon, resulting in an increase of the motor response induced by PAG. Other studies have shown that the activation of TLR4 by LPS increases the biosynthesis of CSE and H 2 S in mouse macrophages through p38/MAPKs and NF‐κB signaling . On the contrary, LPS decreased CSE expression in human endothelial cells and blocked H 2 S production in mouse aorta tissues .…”
Section: Discussionmentioning
confidence: 90%
“…46). For example, GYY4137-associated inhibition of LPS-induced macrophage activation and bleomycin-induced pulmonary fibrosis was dependent on decreased NF-κB induction4748. Transcription factors belonging to the IRF and NF-κB families play a significant role in the pathogenesis of influenza A virus infections by mounting an inflammatory response through TLR3 and RIG-I activation by viral RNA1927, similar to other viruses including paramyxoviruses49505152.…”
Section: Discussionmentioning
confidence: 99%